Hydrogeochemical Assessment of Asunle Waste Dumpsite, Obafemi Awolowo University Campus, Southwestern Nigeria - Konwea, Charles Ikechukwu; Erusiafe, Opeyemi O. (Geological Agency, 2025)
The soil and surface water around the Asunle dumpsite, Obafemi Awolowo University Campus, Ile-Ife, Osun State, southwestern Nigeria, were assessed in this study with a view to determining the contaminant level of heavy metals in the soils and surface water. Geophysical investigation revealed that the area was underlain by four subsurface layers of topsoil, weathered layer, partially weathered or fractured layer, and fresh basement. Sampling and analysis of the topsoil and weathered layer revealed that the hydraulic conductivity of the soils was classified as medium, decreases with depth, and the materials are semipervious. The hydraulic conductivity of the soil influences heavy metal transport. Hence, there is a marked variation in the concentrations of heavy metals around the dumpsite, with most concentrations above the maximum permissible limits recommended. Heavy metals and faecal microbial organisms have contaminated the subsoil and surface water around the Asunle dumpsite. The contamination levels ranged from low to very high. The study concluded that the soils around the Asunle dumpsite are contaminated by heavy metals, which have deteriorated the chemical and microbial qualities of the Asunle stream.